2020
DOI: 10.1101/2020.08.27.270793
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Pharmacodynamic-Toxicodynamic Relationship of AUC and CMAX in Vancomycin Induced Kidney Injury in an Animal Model

Abstract: BackgroundVancomycin induces exposure-related acute kidney injury. However, the pharmacokinetic-toxicodynamic (PK-TD) relationship remains unclear.MethodsSprague-Dawley rats received IV vancomycin doses of 300mg/kg/day and 400mg/kg/day, divided once, twice, thrice or 4xdaily (i.e., QD, BID, TID or QID) over 24-hours. Up to 8-samples were drawn during the 24-hour dosing period. Twenty-four-hour urine was collected and assayed for kidney injury molecule-1 (KIM-1). Vancomycin was quantified via LC-MS/MS. Followin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Vancomycin, the most commonly used antimicrobial agent globally, induces renal toxicity (Avedissian et al, 2021). It was shown that vancomycin (200 mg/kg, given i.p.…”
Section: Pharmaceuticalsmentioning
confidence: 99%
“…Vancomycin, the most commonly used antimicrobial agent globally, induces renal toxicity (Avedissian et al, 2021). It was shown that vancomycin (200 mg/kg, given i.p.…”
Section: Pharmaceuticalsmentioning
confidence: 99%
“…Vancomycin induced kidney injury (VIKI) is a concentration-driven process, with area under the concentration curve (AUC) and maximum concentrations best correlating with the extent of kidney damage. (8)(9)(10)) Studies indicate that rates of VIKI were approximately 5-7% when troughs were maintained between 5-10 mg/L as the standard of practice. (27,43,46) With the publication of the 2009 consensus vancomycin guidelines that promoted more aggressive dosing (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the availability of a reliable and accurate pre-clinical VIKI model will identify vancomycin dosing schemes associated with the lowest risk of VIKI, determine if ameliorating agents can minimize the risk of VIKI with vancomycin exposures required for efficacy, and assess populations in which vancomycin should be avoided (e.g., those receiving other nephrotoxic agents). Our group has utilized a pre-clinical rat model that describes the risk of VIKI as a function of the intensity of vancomycin exposure (9,31,34,39). While our model demonstrates that there is a clear relationship between vancomycin AUC and VIKI in rats, we have yet to determine if our model bridges to humans.…”
Section: Introductionmentioning
confidence: 99%